In vivo and in vitro anti‐diabetic activity of ethanolic propolis extract. Issue 7 (7th May 2020) - El Adaouia Taleb, Rabia; Djebli, Noureddine; Chenini, Hadjer; Sahin, Huseyin; Kolayli, Sevgi
Abstract: The study investigated whether ethanolic propolis extract would exhibit an anti‐diabetic effect in rats. The animals were divided into four groups of five rats each. Diabetic rats received 30% or 15% propolis extract at a dosage of 0.5 ml/100 g for 4 weeks. Data for the diabetic groups treated with 30% and 15% propolis showed a decrease in blood sugar levels from 393 ± 192.7 to 154 ± 28.0 mg/dl and from 386 ± 141.1 to 331.5 ± 123.74 mg/dl, respectively. Compared with the diabetic control group, an improvement was observed in both groups treated with propolis at the pancreatic, hepatic, and renal tissue levels. Antioxidant capacity, phenolic analysis, and the inhibition of α‐amylase and α‐glucosidase were also tested using the propolis samples to support in vivo data. Chrysin and caffeic acid phenyl ester were the dominant phenolics. The IC50 results for α‐amylase (0.62 ± 0.00 μg/ml) and α‐glucosidase (40.40 ± 0.09 μg/ml) were also encouraging. Practical applications: Bee products, non‐synthetic compounds including propolis, are of great interest due to their potential therapeutic effects in metabolic disorders. The current study was designed and is now reported in order to confirm this potential benefit. The results obtained indicate that the higher concentration (30%) of ethanolic propolis extract exhibited excellent potential anti‐diabetic activity by reducing blood sugar levels in diabetic rats. In addition, compared to the diabetic rat group, this extract exhibited a promising effect on the pancreatic, hepatic, and renal tissues of the propolis‐treated groups. The current results indicate that propolis is a remarkable natural product with clinical potential in the treatment of diabetic disease. Abstract : In the current study, propolis was evaluated as a possible anti‐diabetic agent thanks to in vitro and in vivo data. It was emphasized that ethanolic propolis extract significantly decreased the blood sugar level in diabetic rats and it showed a promising effect on the tissue of pancreatic, hepatic, and renal. As a consequence of the experimental analysis and biochemical evaluations, the studied doses of ethanolic extracts could be consumed as a natural product against diabetes disease.